2015
DOI: 10.1016/j.jaci.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of glutathione S-transferase allergen cross-reactivity in a North American population: Relevance for molecular diagnosis

Abstract: Background It is not clear if cross-reactivity or co-sensitization to glutathione S-transferases (GST) occurs in tropical and subtropical environments. In the United States, Bla g 5 is the most important GST allergen, and lack of co-exposure to GST from certain species allows a better assessment of cross-reactivity. Objectives To examine the molecular structure of GST allergens from cockroach (Bla g 5), dust mites (Der p 8, Blo t 8) and helminth (Asc s 13) for potential cross-reactive sites, and to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 37 publications
6
57
0
1
Order By: Relevance
“…These two IgE-reactive peptides of Rhi o 1 were not conserved in other allergen sequences (data not shown) and therefore probably non-cross-reactive in nature. Our study sustains the lower clinical relevance of cross-reactivity between moderately conserved allergens (37). Therefore, epitope information generated in this study may be sufficient for the molecular diagnosis of Rhi o 1 allergy and may not be compromised due to its cross-reactivity with Bla g 2.…”
Section: Discussionsupporting
confidence: 80%
“…These two IgE-reactive peptides of Rhi o 1 were not conserved in other allergen sequences (data not shown) and therefore probably non-cross-reactive in nature. Our study sustains the lower clinical relevance of cross-reactivity between moderately conserved allergens (37). Therefore, epitope information generated in this study may be sufficient for the molecular diagnosis of Rhi o 1 allergy and may not be compromised due to its cross-reactivity with Bla g 2.…”
Section: Discussionsupporting
confidence: 80%
“…The group 8 allergen (GST) of B. tropicalis was identified in 1996 by screening of a B. tropicalis cDNA library and it was later produced as a recombinant protein [60,61,62]. While Blo t 8 has been shown to be clinically relevant in Colombia [60,62], in the USA and Singapore the IgE reactivity to this allergen has been reported to be very low [11,61].…”
Section: Allergens Of B Tropicalismentioning
confidence: 99%
“…While Blo t 8 has been shown to be clinically relevant in Colombia [60,62], in the USA and Singapore the IgE reactivity to this allergen has been reported to be very low [11,61]. Structural models of Blo t 8, and of Asc l 13, the GST of A. lumbricoides , revealed several patches of conserved and surface-exposed residues, suggesting the existence of cross-reactive and species-specific epitopes [60].…”
Section: Allergens Of B Tropicalismentioning
confidence: 99%
“…[116][117][118][119][120][121][122][123][124][125][126][127][128] We have demonstrated that helminth infection can be associated with increased IgE responses to many different allergens, especially those structurally related to parasite antigens. 116 Individuals infected with filarial parasites were shown to have higher levels of IgE against HDM and cockroach extracts (that have several major allergens with homologues in filarial parasites) but not against timothy grass extract, an allergen extract with just a few minor allergen homologues in helminths.…”
Section: -89mentioning
confidence: 99%